Potencial de rendimento, qualidade industrial e fisiológica de sementes de trigo cultivado em diferentes regiões tritícolas - Kehl, Kassiana (2013)
Wheat is mainly focused on the supply to the food industry, mainly consumed in the form of by-products, breads, pasta, cakes and biscuits. In this context, it becomes important in the commodity market, which selects cultivars of high yield potential and meets industry requirements. The potential yield, industrial and physiological quality of the seed industry are directly related to the establishment of plants, climatic conditions, soil, crop management, harvesting point and storage. The aim of this study was to evaluate the agronomic and industrial potential and the physiological quality of seeds of wheat cultivars of different commercial grades produced in two wheat growing regions of the state of Rio Grande do Sul. The experiments were conducted in Cachoeira do Sul (Wheat Growing Region II) and Júlio de Castilhos (Wheat Growing Region I). The cultivars under analysis and tested were Ametista, BRS Louro, Fundacep Nova Era, Topázio, TBIO Mestre and TBIO Pioneiro 2010. Sowing in Cachoeira do Sul was held on May 22 and in Júlio de Castilhos held on June 5, 2012, adopting the randomized complete blocks with three replications with plots of 5.0 m2. The harvest of experiments was made in October and November of the same year. Immediately after harvest were conducted analyzes of yield components have been made. Three months after it was made the analysis of industrial quality and six months after harvest determined the germination and how strong the plants are at that moment. The agronomic potential in the region of Júlio de Castilhos, cultivars provided the highest yield; hectoliter weight and thousand seed weight than those conducted in Cachoeira do Sul. The industrial quality of wheat produced in Cachoeira do Sul was better than at Júlio de Castilhos. Germination and strongest did not differ for local driving. Cultivars have themselves characters that may express and present greater or lesser aptitude for industrial quality, yield potential and stability depending on the environment in which they are exposed. The regions of Júlio de Castilhos and Cachoeira do Sul, proved marginal for seed production of wheat cultivars tested.